The Long-Term Effects of Measles Vaccination on Earnings and Employment: Comment - Michael Wiebe (Institute for Replication (I4R), 2024)
Atwood (2022b) reports a positive effect of the 1963 measles vaccine on long-run economic outcomes. The identifying variation is from pre-vaccine average reported measles incidence, but this plausibly represents reporting capacity or initial health levels, rather than actual disease incidence. I extend the sample and use an event study to test for differential trends, and find trends that are inconsistent with a treatment effect of the vaccine.
Keywords: I12; I18; J22; J24; J31; 330